2010
DOI: 10.1016/j.bbrc.2009.12.115
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling in pancreatic endocrine cell and diabetes

Abstract: Recent studies have improved our understanding of the physiological function of Notch signaling pathway and now there is compelling evidence demonstrating that Notch is a key regulator of embryonic development and tissue homeostasis. Although further extensive studies are necessary to illustrate the molecular mechanisms, new insights into the role of Notch signaling in pancreas development and diabetes have been achieved. Importantly, the ability to regulate Notch signaling intensity both positively and negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 40 publications
2
44
0
Order By: Relevance
“…Luciferase reporter assay and rescue experiment confirmed that miR-613 targets 3′UTR of notch3 to suppress the expression of notch3 and inhibits pancreatic cancer proliferation. Notch 3 is a protein that in encoded by the NOTCH3 gene in human and is one of the important mediators in the Notch signaling pathway, which has been shown to maintain a pool of pancreatic progenitor cells at the early stage of pancreatic development, and governs pancreatic ductal cell differentiation [29]. Notch3 has been shown to be overexpressed in several types of cancers, which makes it a promising therapeutic target for cancer treatment [30].…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase reporter assay and rescue experiment confirmed that miR-613 targets 3′UTR of notch3 to suppress the expression of notch3 and inhibits pancreatic cancer proliferation. Notch 3 is a protein that in encoded by the NOTCH3 gene in human and is one of the important mediators in the Notch signaling pathway, which has been shown to maintain a pool of pancreatic progenitor cells at the early stage of pancreatic development, and governs pancreatic ductal cell differentiation [29]. Notch3 has been shown to be overexpressed in several types of cancers, which makes it a promising therapeutic target for cancer treatment [30].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the inhibition of the hedgehog signals also leads to the ectopic appearance of the pancreatic structures in the organs such as the stomach and duodenum (45) indicates that this system also plays a role in determining the area in which the pancreas will develop. It has been shown that Notch signals stimulate exocrine cell differentiation, but suppress endocrine cell differentiation (46). Follistatin and FGF are also involved in the development of exocrine pancreatic progenitors (47).…”
Section: Pancreas Developmentmentioning
confidence: 99%
“…Studies in mouse (reviewed by Kim et al, 2010) and fish (reviewed by Tiso et al, 2009) have implicated Notch signaling in regulating differentiation of pancreatic progenitors. We have previously identified a population of pancreatic Notch-responsive cells (PNCs) within the pancreatic duct ).…”
Section: Genetic Inducible Fate Mapping Of Notchresponsive Cells Of Tmentioning
confidence: 99%